Performance measurement using dpdk in software-defined local and wide area networks - hyeon Kim, Ki; Kim, Dongkyun; Hwan Kim, Yong; Kim, Joobum (International Journal of Engineering and Technology, 2018)
Background/Objectives: For data center-based enterprises, the use of data traffic continues to increase. As a result, the increasingly efficient processing of increasing data traffic is becoming a major issue. Effective processing of traffic can be performed through the addition of physical network equipment, but this requires considerable costs.Methods/Statistical analysis: To solve this problem, researches on server virtualization and network virtualization technology are being actively conducted. However, while network virtualization is a cost-effective solution, open-source virtual switches used in network virtualization technologies have the performance penalty because they handle packets at the kernel of server's operating system. As a result, the Intel has developed the Data Plane Development Kit (DPDK) technology to address the performance degradation of the operating system.Findings: In this paper, we propose the DPDK performance test environment based on Open Virtual Switch (OVS) to verify the stability and performance of the DPDK-oriented virtualization technology, in association with a new KREONET-S project which aims tothe softwarization of the Korea Research Environment Open Network (KREONET) infrastructure.Improvements/Applications: We perform conducted experiments on Software-Defined Local Area Network (LAN) and Wide Area Network (WAN) environment using KREONET-S show the result.Â Â